Induction of Apoptosis Scutellaria baicalensis Georgi Root Extract by Inactivation of the Phosphatidyl Inositol 3-kinase/Akt Signaling Pathway in Human Leukemia U937 Cells - Choi, Eun Ok (J Cancer Prev, 2019)
BACKGROUND: The roots of Scutellaria baicalensis Georgi (Labiatae) have been widely used in traditional medicine for treatment of various diseases. In this study, we investigated the effects of ethanol extracts of S. baicalensis roots (EESB) on the growth ofn human leukemia U937 cells. METHODS: The effect of EESB on cell viability was measured by the 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide assay. Apoptosis was determined using 4,6-diamidino-2-phenyllindile staining and flow cytometry. The effects of EESB on the expression of regulatory proteins of apoptosis and phosphatidyl inositol 3-kinase (PI3K)/Akt signaling were determined by Western blotting. Caspase activity and mitochondrial membrane potential (MMP) were measured using flow cytometric analysis. RESULTS: EESB significantly inhibited the growth of U937 cells and induced apoptosis, which was associated with down-regulation of anti-apoptotic Bcl-2, up-regulation of pro-apoptotic Bax, the loss of MMP and activation of caspase-9 and -3. We also found that EESB enhanced the expression of death receptors (DRs) and their associated ligands and induced the activation of caspase-8 and truncation of Bid. In addition, EESB suppressed PI3K/Akt signaling and EESB-induced apoptosis and growth inhibition were further increased by inhibition of PI3K activity. CONCLUSIONS: Our results indicated that the pro-apoptotic effect of EESB was mediated through the activation of DR-mediated intrinsic and mitochondria-mediated extrinsic apoptosis pathways and inhibition of the PI3K/Akt signaling in U937 cells.